The Influence of Placement and Competence on the Performance of Civil Servants through Motivation at the Regional Civil Service Agency of Jambi Province - Niawati, Wisnilili; Yamali, Fakhrul Rozi; Hapsara, Osrita (Dinasti Publisher, 2025)
The purpose of this study is to analyze the effect of placement and competence on motivation, as well as to analyze the effect of placement and competence on performance, and to analyze the effect of placement and competence on performance through motivation at the Regional Civil Service Agency of Jambi Province. The method used in this research is descriptive-verificative and quantitative statistics, with questionnaire tabulation from respondents’ answers as the basis for descriptive statistical processing, and quantitative methods using Structural Equation Modeling (SEM) with SmartPLS 3.0 as the analytical tool. Based on the analysis results using SmartPLS 3.0, it was found that placement has a significant effect on motivation; competence has a significant effect on motivation; placement does not have a significant and positive effect on employee performance; competence has a positive and significant effect on employee performance; motivation has a positive and significant effect on employee performance; placement has a significant effect on employee performance through motivation; and competence has a significant effect on employee performance through motivation